RELEVANSI HADITS AHKĀM AL-USRAH DALAM PEMBENTUKAN HUKUM KELUARGA ISLAM KONTEMPORER - M. Khoirul Muzakki; Muhammad Qoiruman Afandi (Jurnal Hukum Keluarga Islam El-Qisth, 2024)
Family law hadiths, considered the second source of Islamic law after the Quran, are of paramount importance in shaping family law in Islam. However, they are often interpreted literally, detached from their historical context. This study aims to analyze the classification of family law hadiths, explore their essential meanings through the methodology of hadith interpretation, and assess their relevance in formulating contemporary Islamic family law. The study employs a qualitative approach based on a literature review, analyzing family hadiths in authoritative hadith collections, as well as in contemporary Islamic jurisprudence and thought. The findings demonstrate that family law hadiths serve diverse legal functions, oriented towards ethical values ​​such as justice, responsibility, and family protection. By integrating the methodologies of hadith interpretation and the objectives of Islamic law (maqasid al-shari'ah), the study establishes the significance of these hadiths and their adaptability to the challenges of contemporary Islamic family law. This study underscores the importance of contextual reading of hadiths as a foundation for formulating a just and public-interest-oriented Islamic family law.